Body Mass Index and Surgical Outcome in a Puerto Rican Population - Cruz, Norma I.; Lopez, Luis A.; Santiago, Elvis (Puerto Rico Health Sciences Journal, 2018)
Objectives: To determine the impact of body mass index (BMI) on postoperative morbidity and 30-day mortality in the population served by the University of Puerto Rico (UPR)-affiliated hospitals. Methods: We reviewed the surgical data entered into the UPR General Surgery Department database from January 1, 2014, through June 30, 2016. This database collects patient and procedural information from the UPR-affiliated hospitals. We compared the postoperative morbidity and 30-day mortality rates of 5 different BMI groups: underweight (<18.5 kg/m2), normal weight (18.5–24.9 kg/m2), overweight (25.0–29.9 kg/m2), obese, classes I and II (30–39.9 kg/m2), and morbidly obese (≥40 kg/m2). Multivariable regression analyses, adjusted for age, gender, and surgery type, were used to evaluate the risks for each BMI category. Results: Information on 9,856 patients was reviewed. The mean age of the sample population was 52 (±20) years; 57% were women and 43% were men. The postoperative morbidity and 30-day mortality rates of the underweight group were significantly higher than those of the normal-weight group (6.1% vs. 3.1% and 2.1% vs. 0.5%, respectively; p<0.001). The morbidly obese also had significantly higher (p<0.001) postoperative morbidity (5.3% vs. 2.1%) and 30-day mortality rates (2.7% vs. 0.5%) compared to normal-weight patients. The odds of 30-day mortality were significantly higher for the underweight (odds ratio [OR], 5.64; 95% confidence interval [CI], 2.47–12.92) and morbidly obese patients (OR, 7.23; 95% CI, 3.01–17.39). The overweight patients had no increased risk, and the obese patients had a slight increase in morbidity (OR, 1.54; 95% CI, 1.08–2.21) but no significant increase in 30-day mortality (p>0.05). Conclusion: Patients at the extremes of the BMI have more postoperative complications and higher 30-day mortality rates than do patients with mid-range scores.